2016
DOI: 10.1161/atvbaha.116.307841
|View full text |Cite|
|
Sign up to set email alerts
|

Resveratrol Inhibits Aortic Root Dilatation in the Fbn1 C1039G/+ Marfan Mouse Model

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 46 publications
4
56
1
Order By: Relevance
“…Total RNA was extracted from the carotid arteries by use of TRIzol reagent (TaKaRa Bio Inc., Kusatsu, Japan), and 1 μg of total RNA was reversely transcribed into cDNA according to the manufacturer's directions (TaKaRa Bio Inc., Kusatsu, Japan) (18). The cycle threshold values were measured on the level of β-actin, and the corresponding gene expression was assessed by the 2 −ΔΔCq method.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from the carotid arteries by use of TRIzol reagent (TaKaRa Bio Inc., Kusatsu, Japan), and 1 μg of total RNA was reversely transcribed into cDNA according to the manufacturer's directions (TaKaRa Bio Inc., Kusatsu, Japan) (18). The cycle threshold values were measured on the level of β-actin, and the corresponding gene expression was assessed by the 2 −ΔΔCq method.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%
“…In addition, AP-1 is a heterodimer composed of c-Fos and c-Jun, which is also involved in the process of cell cycle, apoptosis, and proliferation. It is reported that AP-1 could induce proliferation and differentiation in a variety of cells (16)(17)(18). However, the relationship among the RNF10, Meox2, or AP-1 signaling proteins during VSMC proliferation has been not unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These include AT1 receptor blockade, 109,111,112 caspase inhibition, 113 and administration of resveratrol. 114 Although TGF-β signaling activation has been postulated in the aortic pathologies, 102,115 whether inhibition of TGF-β preventing or augmenting TAA in Marfan mouse models has not been consistently reported in the literature. 109,112,116 …”
Section: Thoracic Aortic Aneurysmsmentioning
confidence: 99%
“…Using pharmacological tools to manipulate the renin angiotensin system, there have been consistent demonstrations that losartan attenuates aortic pathology in mice with fibrillin-1 manipulations. [5][6][7][8][26][27][28] However, it has been proposed that losartan may exert these beneficial actions independent of AT1 receptor antagonism. [6][7][8] Additionally, it has been suggested that AngII may not be responsible for cardiovascular pathology in mice with genetically manipulated fibrillin-1.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, randomized control trials of angiotensin receptor blockers have yielded mixed results in Marfan syndrome associated TAA, in contrast to the consistent results that have been generated using mouse models of the disease. [5][6][7][8][26][27][28] Most of the mouse and human studies have been performed using losartan, which is characterized by a relatively short half-life and surmountable antagonism. The deficiencies of this drug were likely to have been ameliorated in mouse studies by consistent delivery, via osmotic pumps and diet, leading to a persistent inhibition.…”
Section: Discussionmentioning
confidence: 99%